Species identification of spider mites (Tetranychidae: Tetranychinae): a review of methods - A. V. Razuvaeva; E. G. Ulyanova; E. S. Skolotneva; I. V. Andreeva (Вавиловский журнал генетики и селекции, 2023)
Spider mites (Acari: Tetranychidae) are dangerous pests of agricultural and ornamental crops, the most economically significant of them belonging to the genera Tetranychus, Eutetranychus, Oligonychus and Panonychus. The expansion of the distribution areas, the increased harmfulness and dangerous status of certain species in the family Tetranychidae and their invasion of new regions pose a serious threat to the phytosanitary status of agroand biocenoses. Various approaches to acarofauna species diagnosis determine a rather diverse range of currently existing methods generally described in this review. Identification of spider mites by morphological traits, which is currently considered the main method, is complicated due to the complexity of preparing biomaterials for diagnosis and a limited number of diagnostic signs. In this regard, biochemical and molecular genetic methods such as allozyme analysis, DNA barcoding, restriction fragment length polymorphism (PCR-RFLP), selection of species-specific primers and real-time PCR are becoming important. In the review, close attention is paid to the successful use of these methods for species discrimination in the mites of the subfamily Tetranychinae. For some species, e. g., the two-spotted spider mite (Tetranychus urticae), a range of identification methods has been developed – from allozyme analysis to loop isothermal amplification (LAMP), while for many other species a much smaller variety of approaches is available. The greatest accuracy in the identification of spider mites can be achieved using a combination of several methods, e. g., examination of morphological features and one of the molecular approaches (DNA barcoding, PCR-RFLP, etc.). This review may be useful to specialists who are in search of an effective system for spider mite species identification as well as when developing new test systems relevant to specific plant crops or a specific region.